Seasonal Variation in the Incidence of Yeast Rotters of Tomato Fruit in Soil and on various Parts of Tomato - Onesirosan, P. T. (Faculty of Agriculture, University of Ife, 2015)
Geotrichum candidum and Pichla Kluyveri, the two important yeasts which incite rots of tomato fruits in southern Nigerian were frequently isolated from field/soil and various parts of the host plant during the wet season but rarely during the dry season. However, the frequency of their isolation remained uniformly high in forest soil in both seasons. G. candidum was isolated from the shoots and roots of seedlings as well as the flowers and fruits; it was also a frequent contaminant of tomato seeds extracted during the wet season. P. Kluyvery on the other hand, was more prevalent on the stems and leaves of mature plants.